Banco de imagens fotográficas: fonte de informação em saneamento básico - CRUZ, Dionatan Sarges (2018)
Study on the creation of a photographic image bank with the objective of analyzing the organization of photographic images in the area of basic sanitation for use as a source of information in the development of technical and scientific activities of the Research and Basic Sanitation Group (GPHS). Of the Federal University of Pará. As a methodological procedure, the research is reflected as exploratory, with a qualitative approach, being a case study. In order to obtain data and collect information on the subject, a bibliographical research on photographic images bank was adopted, as well as meetings with researchers from the GPHS, in which the necessary elements were defined for the database and the identification of the material Available for incorporation into that bank. As results, it was observed that the image bank is an essential tool for the management of photographic images that are important sources of information to be used in diverse works. In addition, nonproprietary BIBLIVRE software was defined for the management of photographic information, and guidelines were drawn up for the creation of a photographic database of basic sanitation images for GPHS. Finally, it is concluded that the appropriate use of an image bank for organizing, storing and managing information is of fundamental relevance for the search and retrieval of information whether proprietary or non-proprietary, since institutions need secure sources for their researches.